Factors associated with successful vaginal birth after cesarean deliveries - Hastuti, Tri Turnianti; Santoso, Agus; Al-Fajri, Galang; Shalihah, Nusaibah Mar’atush; Dina, Aisyah Kafa (Institute of Computer Science (IOCS), 2024)
The high global cesarean section rate, ranging from 10% to 40%, imposes an economic burden at national and individual levels. Due to the increased risk of complications associated with repeated cesarean sections and the safety of vaginal birth after cesarean (VBAC), VBAC has become a preferred strategy. It is crucial to offer mothers appropriate counseling on VBAC, considering potential benefits and risks, as well as understanding other factors influencing the choice of childbirth mode. An analytical observational study with a cross-sectional design was conducted, utilizing data from medical records of patients who gave birth at Dr. Tjitrowardojo Hospital Purworejo from January 2022 to December 2022. Data from 108 subjects were analyzed using Chi-square to identify variables correlated with VBAC spontaneous delivery. Mothers who successfully delivered VBAC at a non-risk age numbered 32 (55.6%). Mothers with a parity history of ≥2 who successfully delivered VBAC numbered 47 (45.2%). Mothers who delivered babies with normal birth weight and successfully delivered via VBAC numbered 39 (41.5%). Abnormal birth weight was significantly associated with VBAC failure (PR=3.526 (1.031-12.062), p=0.036). There were 8 (72.2%) babies with an Apgar score <6 at 5 minutes after VBAC. Abnormal birth weight is associated with the failure of spontaneous VBAC delivery at Dr. Tjitrowardojo Hospital Purworejo.